Improving the capability of MSME actors in preparing basic financial reports in Kedungkandang Village - Irma Hidayati; Umi Nandiroh; Safira Koesherawati; Ghina Abyan Azizah Haris (Universitas Muhammadiyah Magelang, 2022)
The business sector in RW 01 Kedungkandang Malang Village has started to show growth as economic conditions have recovered after the Covid-19 pandemic. MSMEs, however, neglect to document transactions and prepare financial reports because more focus on marketing their products. The aim of this community service is to raise awareness on the importance of accounting records and how to prepare basic financial reports. Program carried out in several stages ranging from socialization, counseling, training, mentoring to monitoring and evaluation. This training and mentoring have succeeded in increasing the understanding and capability of MSME actors to make financial transaction records and basic financial reports independently.